PENGEMBANGAN TES READING FOR ACADEMIC PURPOSES UNTUK PROGRAM EAP DI IAIN SURAKARTA - Imroatus Solikhah (Center of Language and Cultural Studies, 2015)
The objective of this study is to devise standardized test for Reading for Academic Purposes (WAP). The test was focused on WAP as the main competency of reading for EAP and elaborated sub-competencies into literal, inferential, and critical reading. The items of the test were developed from 9 passages before trials to explore critical reading as main academic literacy of EAP program. A quantitative approach was used in this study emphasizing statistical analysis for manual and SPSS program. Subjects of this study for three time trials were 30 students of EAP class at IAIN Surakarta. Each trial involved 10 students. The study revealed that of 40 items of reading test, 24 items derived from 6 passages performed accepted validation showing five criteria: difficulty indexes, degrees of difficulty, distractor effectiveness, validity, and reliability.